Isosorbide Diallyl Based Antibacterial Thiol-Ene Photocured Coatings Containing Polymerizable Fluorous Quaternary Phosphonium Salt - ÇAKMAKÇI, EMRAH; KAHRAMAN, MEMET VEZİR (AMER CHEMICAL SOC, 2019)
The preparation of multifunctional, smart, and environmentally friendly coating materials is an innovative way to answer the needs in both today's and future technologies of coatings. In this work, antibacterial and environmentally friendly photocured coatings were prepared via a thiol-ene photopolymerization technique. First, with the aim to reduce the carbon footprint of the petroleum-based monomers, a greener alternative, isosorbide diallyl ether (IDE), was synthesized. Then a polymerizable fluorinated quaternary phosphonium salt (PFQPS) was synthesized to render the coatings antibacterial. PFQPS was added in different amounts (1%, 3%, 5%, and 10%) to the IDE-based thiol-ene-based formulations, and its effect on the thermal, mechanical, and optical properties were investigated. The prepared coatings exhibited exceptional antibacterial activity against E. coli and S. aureus. When the concentration of the PFQPS was 10%, the zone inhibition diameters were found as 82 +/- 5 and 18 +/- 1.9 for E. coli and S. aureus, respectively.
Keywords: Thiol-ene; Fluorine; Quaternary phosphonium salt; Antibacterial; Isosorbide; CLICK REACTION; NETWORKS; AMMONIUM; FLUORINE; ADHESION; BISMALEIMIDE; SURFACES; DEVICES; SYSTEMS; FILMS